Zur sinnlichen Realität religiöser Praxis in der Aum Shinrikyō und ihrer Bedeutung für die Legitimation religiös begründeter Gewaltanwendungen - Prohl, Inken (Zeitschrift für Religionswissenschaft, 2012)
On March 20, 1995 the Japanese Modern Religious Organization Aum Shinrikyo, which holds to be a Buddhist religion, carried out a gas attack on the Tokyo Subway system. My paper investigates the reasons that motivated a group of well-educated, young Japanese to conduct an assault against their own people in the name of Buddhism. First, Aum Shinrikyo will be put into the framework of contemporary religion in Japan. Next, after an overview on the chain-reaction of violence that was triggered by a rather accidental death, Asaharas interpretation of the teachings of Tibetan Buddhism will be presented. Special attention will be paid to Asaharas rhetoric of poa to legitimize killing in the name of religion. Ascetic practices played a dominant role in Aum Shinrikyo; therefore, they will be treated as »offensives on the senses« that served to transform the teachings of Asahara into religious convictions. The extreme character of the ascetics practices can, as it will be shown, be traced down to special features of contemporary Japanese society. Finally, the conclusion will relate the fascination and power of persuasion of the Aum Shinrikyo to a so-called »New-Age-Buddhism« as well as the pluralistic situation of Buddhism in contemporary Japan.